Body Fat and Health: How Can I Tell if I am at Risk for Health Problems? - Kohrine A. Counts; Anne E. Mathews (EDIS)
Obesity is called an epidemic because there is a high rate of obesity in the United States. In fact, over 30% of all US adults were obese as of 2012, and more than two-thirds are either overweight or obese. This is concerning because excess body fat is linked to poor health and chronic diseases, such as diabetes and heart disease. The amount of excess body fat a person has is commonly sorted into weight status categories using Body Mass Index. This 3-page fact sheet describes the body mass index and how to calculate it. Written by Kohrine A. Counts and Anne E. Mathews, and published by the Food Science and Human Nutrition Department, August 2016.